2019
DOI: 10.31129/lumat.7.1.349
|View full text |Cite
|
Sign up to set email alerts
|

Science at home: parents’ need for support to implement video-based online science club with young children

Abstract: Homes have remarkable possibilities to act as science learning environments for young children (3 - 6 years old). This qualitative case study investigated what kind of support parents need to do online science activities with their children at home. Data consisted of parent’s theme interviews (n=7).  As a main result, a model of parents’ need for support was produced. The model contains three dimensions: 1) the affective dimension, 2) the knowledge and skills dimension and 3) the organizational dimension. Pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
1
0
2
Order By: Relevance
“…The survey results reflect two themes that have emerged in previous research on science education: the importance of parental confidence and potential early differences in science engagement and learning by child gender. Studies across the USA, UK and Scandinavia have reported that parents are enthusiastic about supporting science learning but that they experience anxiety and low confidence in their ability to help their young children (Solomon 2003;McClure et al 2017;Vartiainen and Aksela 2019). Our results show that this lower confidence is present even among highly educated parents and that it results in a lower frequency of informal science-related activities for their young children.…”
Section: Discussionmentioning
confidence: 52%
“…The survey results reflect two themes that have emerged in previous research on science education: the importance of parental confidence and potential early differences in science engagement and learning by child gender. Studies across the USA, UK and Scandinavia have reported that parents are enthusiastic about supporting science learning but that they experience anxiety and low confidence in their ability to help their young children (Solomon 2003;McClure et al 2017;Vartiainen and Aksela 2019). Our results show that this lower confidence is present even among highly educated parents and that it results in a lower frequency of informal science-related activities for their young children.…”
Section: Discussionmentioning
confidence: 52%
“…Данные ранее проведенных исследований показывают, что российская молодежь в среднем больше двух раз меняет свое место работы и 40,3 % экономически активного населения страны работали или в настоящее время работают в неформальном рынке труда 14 . По данным официальной статистики Казахстана, 30 % молодежи не работают по специальности 15 Результаты ранних исследований мотивов российской молодежи при выборе профессии показывают высокую значимость интереса к профессии, далее следует оплата труда и социальная значимость профессии [34]. Результаты ранних казахстанских исследований свидетельствуют, что молодежь рассматривает цель университета с точки зрения его экономической ценности, т. е. в качестве ресурса, позволяющего расширить возможность трудоустройства и улучшить финансовое благополучие.…”
Section: обсуждение и заключениеunclassified
“…27, № 2. 2023 МОНИТОРИНГ ОБРАЗОВАНИЯ по яв ля ет ся только в одной ра бо те как описа ние кей са для вы яв ле ния эф фек тив ных спо со бов под дер жки ро ди те ля ми де тей для уча стия в ди стан ци он ных круж ках на до му [34].…”
Section: вве де ниеunclassified